Angular selectivity based on a double-resonance periodic array of scatterers - Zhou, Lin (2022)
A double-resonance periodic array of scatterers is proposed to achieve angular selectivity in this paper. By properly designing the scatterers' structure and dimensions, bandpass and band-stop resonances are produced by the periodic array at the same frequency under the normal and oblique incidences, respectively, resulting in excellent angular selectivity. The periodic array consists of two identical scatterer layers stacked together with an air spacer. To demonstrate the design concept, a sample of the periodic array with an operating frequency of 10 GHz is designed for the angular selectivity of TE-polarized incident waves. Measurements of the sample are conducted for verification. The simulated and measured results both show good angular selectivity with high transmission under the normal incidence and low transmission under the oblique incidence of large angles.